2016
DOI: 10.7461/jcen.2016.18.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Procedure-related Complication Rate for the Endovascular Treatment of Aneurysmal Subarachnoid Hemorrhage under Local Anesthesia

Abstract: ObjectiveTo report the procedure related complication rate of endovascular treatments (EVTs) performed on patients with aneurysmal subarachnoid hemorrhage (aSAH) under local anesthesia (LA).Materials and MethodsThis study enrolled 186 patients who underwent EVT for ruptured aneurysm under LA from January 2009 to December 2013. Procedure-related complications rate and factors associated with it were analyzed depending on the patients' factors, aneurysm factors and physician factors.ResultsAmong the 186 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…In a retrospective study of 189 patients with SAH, the rate of IPR was significantly higher under local anesthesia than general anesthesia 13. This was a result of unexpected patient motion and occurred in accordance with the unexpected movement.…”
Section: Discussionmentioning
confidence: 95%
“…In a retrospective study of 189 patients with SAH, the rate of IPR was significantly higher under local anesthesia than general anesthesia 13. This was a result of unexpected patient motion and occurred in accordance with the unexpected movement.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, emergent surgery may be a risk factor for the same reason. A previous analysis16 showed that treating a ruptured aneurysm under local anesthesia was inappropriate, with unexpected movement of the patients and the micro-instruments likely the main reason. Another previous study17 showed that small aneurysms were a predictor of IPR, and our data agreed.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of the biomarkers analyzed separately are low, but they have increased when combined [13]. Serum levels of Vascular Endothelial Growth Factor A (VEGF-A) in patients diagnosed with SAH are measured to assess the correlation between VEGF-A and the clinical condition of patient [14, 15]. The assessment of coagulation system and fibrinolysis parameters during the SAH shows the activation of these systems and it is sufficient in the evaluation of thromboembolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Serum level VEGF-A in patients diagnosed with SAH is measured to assess the correlation between VEGF-A and the clinical condition of a particular patient. This may help with proper therapeutics and better prognosis [14, 15].…”
Section: Introductionmentioning
confidence: 99%